Plasticidade de Acacia mangium willd. submetida à deficiência hídrica e à reidratação - Fernandes, Hallefy Elias (Universidade Federal do Tocantins, 2018)
Tocantins, which once adopted forestry as an alternative, is already in the process of being announced as one of the state's largest sources of income. Faced with this, factors such as the conditions of edaphoclimatic conditions may hinder the growth and development of some plants. Plant growth is associated with several physiological and biochemical factors, which are controlled and influenced by genetic specificity of each species and environmental issues. Aiming to investigate the adaptive mechanisms of the Acacia mangium Willd species. The main sources related to availability, as well as the evaluation of the physiological, biochemical and tolerance of the species Acacia mangium Willd. exposed to water deficiency and rehydration. Two experiments were installed. The experiments were conducted in a protected environment at the Experimental Station of the Federal University of Tocantins, Campus of Gurupi-TO. Seedlings with 180 days of age were used, as were transferred to 5.5 liter polyethylene vessels. The statistical design used in the two experiments was completely randomized (DIC), represented by four water treatments (100, 60, 40 and 30% of field capacity) with 12 replications. The first experiment as plants were kept under water deficit during the 25 days of experiment. The second experiment as plants were rehydrated after a short period of water stress of 6 days, raising all water levels to 100% of the field capacity, being evaluated during the 25 days of experiment. During the experimental period, a specialized journal on gas exchanges, potential water leaflet, water content, activity of antioxidant enzymes, proline and dry leaf, stem, root and total masses was carried out. Water stress at 40 and 30% field capacity for 25 days influenced the water relations of Acacia mangium Willd., Reducing leaf water potential, stomatal conductance, transpiration, carboxylation efficiency (A / CI) and energy efficiency (US) to ensure the functioning of biochemical and metabolic processes. Exposure of the seedlings at 60% field capacity did not negatively affect the net assimilation (A), since there was not much variation compared to the control with 100% field capacity. The Acacia mangium Willd. is moderately tolerant to low levels of non-soil water. On the production of dry matter in seedlings of Acacia mangium Willd. a variable more sensitive to water deficit for the dry mass of the leaves and the stem. The treatment with higher water deficit with 30% of the field capacity presented the highest accumulation of the proline content. It is a species under conditions of six days under water stress, it is still able to recover the physiological performance, characterizing its physiological and biochemical plasticity in the molting phase. For a species of Acacia mangium Willd., A catalase for a major enzyme in combating oxidative stress when submitted to water deficit.